Informal caregivers’ attitude toward dementia: the impact of dementia knowledge, confidence in dementia care, and the behavioral and psychological symptoms of the person with dementia : a cross-sectional study - Teichmann, Birgit; Gkioka, Mara; Kruse, Andreas; Tsolaki, Magda (Journal of Alzheimer's disease, 2022)
Background: Dementia is rapidly increasing worldwide due to demographic aging. More than two-thirds of patients are cared by family members. The quality of care depends on the caregivers’ attitude toward dementia influencing patient care decisions. Objective: The aim of this study is to examine the factors that influence the caregivers’ attitude and whether there is an association between participation in a psycho-educational program and attitude. Methods: We performed a cross-sectional study using a structured closed-ended questionnaire to retrieve socio-demographic information from caregivers and the persons with dementia (N=86). The study included validated scales such as the Dementia Attitude Scale, the Dementia Knowledge Assessment Tool 2, the Positive Aspects of Caregiving, the Zarit Burden Interview, the Confidence in Dementia Scale, and Spielberger’s State-Trait Anxiety Inventory, as well as a neuropsychological battery to assess the condition of people with dementia. Results: Our final model explains 55.6% of the total variance and shows a significant correlation of five factors with attitude toward dementia: confidence, behavioral and psychological symptoms of dementia, anxiety as a trait, positive aspects of caregiving, and dementia knowledge. The caregivers who participated in a psycho-educational program showed a significantly more positive attitude toward dementia, better dementia knowledge, higher confidence in dementia care, and lower anxiety as a state. Conclusion: The strong correlation of attitude and knowledge, as well as confidence in dementia care, supports the tripartite model of attitude, which hypothesizes the interrelation of affect, cognition, and behavior.